Empowerment of Posyandu Delima 33 Cadres in Managing Community-Based Waste for Stunting Prevention in Lorok Pakjo Subdistrict, Ilir Barat I District, Palembang CitySubdistrict, Ilir Barat I District, Palembang City - Dasmadi, Dasmadi; Serli Lestari; Husin, Ns.; Saputra, Tedy Setiawan; Abid Khotibul Umam; Prengki; Muhammad Al Azid (Edumedia Solution, 2026)
This community service activity aims to enhance the capacity and role of Posyandu Delima 33 cadres in community-based waste management as an effort to prevent stunting in Lorok Pakjo Subdistrict, Ilir Barat I District, Palembang City. The problems faced by the community include low awareness of household waste management and a lack of understanding of the relationship between environmental cleanliness and the incidence of stunting in children. Through this activity, training, mentoring, and education were provided to Posyandu cadres on the 3R concept (Reduce, Reuse, Recycle), composting of organic waste, and the utilization of inorganic waste as educational media for stunting prevention. In addition, the activity initiated the establishment of a mini waste bank as a platform for environmentally based family economic empowerment. The methods used included a participatory approach through lectures, discussions, hands-on practice, and evaluation of activity achievements. The results showed an increase in the cadres’ knowledge and skills in waste management, as well as increased community awareness of the importance of a clean environment in preventing stunting. This activity also strengthened synergy between higher education institutions, local government, and the community in creating a healthy, sustainable, and stunting-free environment. Keywords community empowerment; posyandu; waste management; stunting; waste bank.